Test of Variant of Knife Edge Shape on Mechanical Coconut Peeler - Agus Roy Butar-Butar; Saipul Bahri Daulay; Lukman Adlin Harahap; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was done to test the variant of the knife edge shape on the effective capacity of the equipment, percentage of material unpeeled, and fuel consumption on mechanical coconut peeler. This research was using non factorial completely randomized design. It was found that the effective capacity of the equipment, percentage of material unpeeled, and fuel consumption were 231.24 unit hour-1, 6,67%, and 2.37 litre hour-1 respectively triangle knife edge,  301.97 unit/hour, 13.33%, and 2.62 litre/hour respectively cone knife edge, and 192.48 unit hour-1, 13.33% and 1.85 litre hour-1 respectively nail knife edge. The results showed that the variant of knife edge had significant effect on the effective capacity and fuel consumption and had no effect on the percentage of material unpeeled. Key words: knife edge, peeler, coconut